Pirfenidone Attenuates the EMT Process and the Secretion of VEGF in TGF-β2-Induced ARPE-19 Cells via Inhibiting the Activation of the NF-κB/Snail Signaling Pathway. (30th January 2023) - Li, Hongsong; Wang, Lijun; Shao, Meilin; Ren, Meimei; Zhang, Wenyi; Zhou, Jian; Wang, Jianming
Abstract : Aim . Pirfenidone (PFD), an antifibrotic drug, has various beneficial functions such as antioxidant, antifibrotic, and anti-inflammatory effects. This study aimed to explore the molecular mechanisms underlying how PFD modulates retinal pigment epithelial (RPE) cells involved in neovascularization and subretinal fibrosis. Methods . ARPE-19 cell lines were treated with transforming growth factor-beta 2 (TGF- β 2) alone or in combination with PFD. RPE cell viability, as a consequence of PFD use, was determined by the CCK-8 assay. Cell migration was assessed by the wound closure assay and quantified by the Image J software. Protein expression of the following markers was measured by the western blot analysis: an epithelial cell marker and E-cadherin; mesenchymal cell markers, fibronectin, matrix metalloprotein-9 (MMP-9), and alpha-smooth muscle actin ( α -SMA); a fibrotic marker and connective tissue growth factor (CTGF); an angiogenesis marker and vascular endothelial growth factor (VEGF); NF- κ B/Snail. The mRNA levels of fibronectin and α -SMA were determined by quantitative real-time PCR. VEGF was quantitatively measured by the enzyme-linked immunosorbent assay. Results . The cell viability assay revealed that PFD had no significant cytotoxic effect on RPE cells at concentrations of less than 1 mg/mL. The cell scratch assay showed that TGF- β 2 stimulation significantly improved the migration of RPE cells and that PFD attenuated this effect. PFD significantly inhibited the TGF- β 2-induced protein expression of E-cadherin and increased the TGF- β 2-induced protein expression of fibronectin, MMP-9, α -SMA, CTGF, and VEGF in ARPE-19 cells. The mRNA expression of fibronectin and α -SMA was inhibited by PFD in TGF- β 2-inducedARPE-19 cells. Additionally, the increased intracellular and supernatant expression of VEGF protein was suppressed by PFD. Mechanistically, RPE cells treated with PFD + TGF- β 2 exhibited a decrease in phosphorylation of the NF- κ B P65 subunit and activation of Snail, compared with the RPE cells treated with TGF- β 2 alone. Conclusion . PFD ameliorated TGF- β 2-induced neovascularization and fibrosis by suppressing the NF- κ B/Snail signaling pathway. Therefore, PFD may be a potential drug in the treatment of age-related macular degeneration.